Acute recurrent distal glossitis. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
Migratory glossitis is the most frequent glossitis in children; it is asymptomatic and characterized by reddened areas surrounded by whitish margins: it extends centrifugally, taking on a geo-graphical appearance. Migratory glossitis has a chronic-recurrent course with initially close relapses, that distance themselves over time until they disappear. Moreover, there are symptomatic acute glossitis; the best known in children is the generalized strawberry glossitis of some infectious diseases, especially streptococcal scarlet fever. Then there is a rarer form of eruptive lingual papillitis affecting one or more very evident fungiform papillae; this form is symptomatic and not recurrent: there is a contagious family variety (1) and a non-contagious variety (2). The current case is characterized by the acute recurrent course, by the intense subjective symptomatology and by the distal involvement of the tongue.